2000
DOI: 10.1128/aem.66.12.5460-5468.2000
|View full text |Cite
|
Sign up to set email alerts
|

Homoduplex and Heteroduplex Polymorphisms of the Amplified Ribosomal 16S-23S Internal Transcribed Spacers Describe Genetic Relationships in the “ Bacillus cereus Group”

Abstract: Bacillus anthracis, Bacillus cereus, Bacillus mycoides, Bacillus pseudomycoides, Bacillus thuringiensis, and Bacillus weihenstephanensis are closely related in phenotype and genotype, and their genetic relationship is still open to debate. The present work uses amplified 16S-23S internal transcribed spacers (ITS) to discriminate between the strains and species and to describe the genetic relationships within the "B. cereus group," advantage being taken of homoduplex-heteroduplex polymorphisms (HHP) resolved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
157
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 67 publications
10
157
0
2
Order By: Relevance
“…Length polymorphism analysis of amplified ITS regions has been used as an efficient tool for species differentiation by several authors (Mora et al, 1997;Tyrrell et al, 1997;Daffonchio et al, 2000) but it was not applicable for the differentiation of several species of dairy streptococci including those analysed in this study. A single ITS amplification product of about 350 bp was detected in S. thermophilus and S. salivarius strains using a standard agarose gel electrophoresis as previously reported by Tilsala-Timisjärvi & Alatossava (1997) and by Moschetti et al (1998).…”
Section: Resultsmentioning
confidence: 99%
“…Length polymorphism analysis of amplified ITS regions has been used as an efficient tool for species differentiation by several authors (Mora et al, 1997;Tyrrell et al, 1997;Daffonchio et al, 2000) but it was not applicable for the differentiation of several species of dairy streptococci including those analysed in this study. A single ITS amplification product of about 350 bp was detected in S. thermophilus and S. salivarius strains using a standard agarose gel electrophoresis as previously reported by Tilsala-Timisjärvi & Alatossava (1997) and by Moschetti et al (1998).…”
Section: Resultsmentioning
confidence: 99%
“…Principally distinguished genetically by plasmids, it has been suggested that B. cereus, B. thuringiensis, and B. anthracis could be considered one species (Daffonchio et al, 2000;Helgason et al, 2000), or at least, are very closely related (Vilas-Boas et al, 2002). These organisms may even occupy overlapping ecological niches.…”
Section: Introductionmentioning
confidence: 99%
“…It includes B. cereus, a species often associated with food-borne disease, Bacillus thuringiensis, which is used as a biological pesticide worldwide, and Bacillus anthracis, a pathogen of warm-blooded animals that can cause the often fatal disease anthrax. Members of the B. cereus group form a highly homogeneous subdivision within the genus Bacillus and it has been proposed that B. cereus, B. thuringiensis and B. anthracis are in fact varieties of the same species (Daffonchio et al, 2000;Helgason et al, 2000). However, B. anthracis and B. thuringiensis differ from B. cereus by containing plasmid-encoded specific toxins and a capsule (B. anthracis only) (Okinaka et al, 1999;Schnepf et al, 1998) and recent studies have shown that B. anthracis is rather monomorphic, whereas there is large diversity within B. cereus and B. thuringiensis (Bavykin et al, 2004;Hill et al, 2004;Priest et al, 2004).…”
Section: Introductionmentioning
confidence: 99%